The Influence of Digital Marketing and Brand Image on Purchase Intention of Local Fashion Products in Surabaya: A Quantitative Study - Hanifah, Anisah Mutiara Zahra (Indonesian Scientific Publication, 2024)
Digital marketing has become a strategic imperative for fashion Micro, Small, and Medium Sized Enterprises (MSMEs) operating in Indonesia’s rapidly digitising urban markets. This study investigates how digital marketing and brand image interact to influence purchase intention for local fashion products in Surabaya. Using a cross sectional online survey of 220 consumers and Partial Least Squares structural equation modelling, the research validates a model where digital marketing directly predicts purchase intention and indirectly affects it through brand image. Results indicate that digital content quality, storytelling, and influencer credibility significantly enhance brand image, which partially mediates the relationship between digital marketing and purchase intention. The model explains 55 % of the variance in purchase intention, highlighting the importance of narrative rich, trust building strategies. Discussion situates these findings within the Theory of Planned Behaviour (TPB), a framework that explains how attitudes, norms, and perceived control shape intention. This highlights dual cognitive and affective pathways, and proposes practical guidelines for MSMEs to leverage storytelling, user generated content, and micro influencer partnerships. The study contributes to emerging market scholarship by evidencing how perceptual and relational mechanisms convert digital stimuli into economic value, and it recommends longitudinal and experimental research to explore temporal effects and contextual moderators.